$\begin{cases} 2x^3 -4x^2 +3x-1=x^3 (30 -56y +36y^2-8y^3) \\ (3x-1)\sqrt{2x^2 y +2xy -2x^2-3}=4x^3 -9x^2 y +\dfrac{23}{2}x \end{cases} $ Hệ thi thử liên trường tỉnh Vũng Tàu

GIẢI

$x=0$ không là nghiệm. Pt1 $\Leftrightarrow t^3-3t^2+4t-2=8y^3-36y^2+56y-30$ với $t=\dfrac{1}{x}$

$\Leftrightarrow (t-1)^3 + (t-1) = (2y-3)^3 + (2y-3)$

Xét hàm số $f(u) = u^3+u;\ u \in \mathbb{R},\ f'(u) = 3u^2 +1 >0$ vậy $f(u)$ đồng biến trên $ \mathbb{R}$

$\Rightarrow t =2y -2$ hay $\dfrac{1}{x}=2y-2 \Rightarrow y=\dfrac{2x+1}{2x}$ thay vào pt2 được

$(3x-1)\sqrt{2x^2 \dfrac{2x+1}{2x} +2x \dfrac{2x+1}{2x} -2x^2-3}=4x^3 -9x^2 \dfrac{2x+1}{2x} +\dfrac{23}{2}x $

$\Leftrightarrow (3x-1)\sqrt{3x-2}= 4x^3-9x^2 +7x$ Điều kiện $x\ge \dfrac{3}{2}$

$\Leftrightarrow (3x-1) \bigg [ x -\sqrt{3x-2} \bigg ] + 4x (x^2-3x+2)=0$

$\Leftrightarrow (3x-1) \dfrac{x^2-3x+2}{x+\sqrt{3x-2}} + 4x (x^2-3x+2)=0$

$\Leftrightarrow (x^2-3x+2) \bigg [ \dfrac{3x-1}{x+\sqrt{3x-2}} + 4x \bigg ]=0$

$\Leftrightarrow x^2-3x+2=0$ hay $x=1;\ x=2$, $\dfrac{3x-1}{x+\sqrt{3x-2}} + 4x >0;\ x\ge \dfrac{3}{2}$

Kết luận $(x;\ y) = (1;\ \dfrac{3}{2});\ (2;\ \dfrac{5}{4})$